PENGARUH MUTASI DAN PROMOSI JABATAN TERHADAP PRESTASI KERJA (STUDI PADA PEGAWAI PT. SILVER SILK TOUR & TRAVEL PEKANBARU) - Diah Mustika Rani Saputri; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted at PT. Silver Silk Tour & Travel Pekanbaru which is located on Kaharuddin Nasution Street No.77, Simpang Tiga Pekanbaru. The problem in this study is that the target of employee promotion has not been achieved in the past five years, this is suspected to have problems in work performance. The purpose of this study was to determine the effect of mutation, promotion of work performance of PT. Silver Silk Tour & Travel Pekanbaru. In this study the method used was quantitative descriptive with the SPSS program. The sample of this study was 40 people taken from the total population. The data obtained from the questionnaire is then processed to be tested through the SPSS 23 program. Testing data analysis using simple and multiple linear regression analysis method. The results of multiple linear regression analysis from this study are Y = 8,786 + 0,445X1 + 0,679X2. The research that has been done shows the results that the respondent's response to mutations and promotion in the category is quite agree while in the work performance on the categorical agree. While the t test that has been carried out shows that the mutation and job promotion variables partially have a significant effect on work performance. The F test results show that simultaneous mutations and job promotions have a significant effect on work performance. As for the calculation of the coefficient of determination (R2) obtained Adjusted R Square of 0.711. This shows that the mutation and promotion have an effect of 71.1% on the work performance of employees of PT. Silver Silk Tour & Travel Pekanbaru. While the remaining 28.9% is influenced by other variables not included in this study.Keywords: Mutation, Job Promotion, and Job Achievement